2019
DOI: 10.1002/hbm.24619
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory alpha oscillation predicts attentional selection and hemodynamic response

Abstract: In covert visual attention, one fundamental question is how advance knowledge facilitates subsequent neural processing and behavioral performance. In this study, with a rapid event‐related simultaneous electroencephalography (EEG) and functional near infrared spectroscopy recording in humans, we explored the potential contribution of anticipatory electrophysiological activation and hemodynamic activation by examining how anticipatory low‐frequency oscillations and changes in oxygenated hemoglobin (HbO) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…providing more ATP) in right PFC with positive benefits for the WM-related FPN network. An alternative explanation is that the neurovascular coupling between hemodynamic activities and EEG plays a role in visual information processing 30, 31 . Thus, further EEG-fNIRS/fMRI studies are necessary to gain a better understanding of the underlying mechanism of beneficial effects from tPBM.…”
Section: Discussionmentioning
confidence: 99%
“…providing more ATP) in right PFC with positive benefits for the WM-related FPN network. An alternative explanation is that the neurovascular coupling between hemodynamic activities and EEG plays a role in visual information processing 30, 31 . Thus, further EEG-fNIRS/fMRI studies are necessary to gain a better understanding of the underlying mechanism of beneficial effects from tPBM.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that contralateral alpha power following feedback was predictive of N2pc amplitudes on the upcoming choice, suggesting that it could be related to subsequent attentional orienting to the next stimulus location. Specifically, preparatory activity in the sensory cortices is thought to facilitate subsequent attentional processing, as it is correlated with subsequent N2pc amplitudes relative to the attended location (Zhao et al, 2019), but also with decreased RTs (van den Berg et al, 2016). Multivariate pattern analyses also recently showed that preparatory contralateral alpha power boosts stimulus processing (Barne et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The N2pc is a lateralized component that is larger on contralateral electrode sites of the attended location, and that shows larger amplitudes if the attended target is associated with reward (Kiss et al, 2009). In addition, N2pc amplitudes are predicted by preparatory alpha oscillations during attentional selection tasks, and are accompanied by alpha oscillations relative to the choice that was made (Zhao et al, 2019, Bacigalupo & Luck, 2019. Thus, the N2pc reflects a neural correlate of attentional processing in space.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A cueinduced alpha reflects attentional selection. Alpha decreases leading to liberalization of alpha when detecting a cue and anticipating a target in visual cueing tasks [19]. However, a warning stimulus would elicit a decrease in alpha [20], [21].…”
Section: Introductionmentioning
confidence: 99%